Development of Abraham model correlations for describing solute transfer into 2-methyl-1-butanol from both water and the gas phase from experimental solubility data of crystalline organic compounds. (2nd September 2020) - Qian, Ellen; Gupta, Avi; Neal, Reese; Lee, Grace; Che, Melanie; Wang, Lainey; Yue, David; Fischer, Rachel; Jodray, Megan; Connolly, Erin; Wang, Shang; Liu, Kelly; et al.
ABSTRACT: Experimental solubilities have been measured at 298.15 K for benzil, biphenyl, pyrene, fluoranthene, acenaphthene, xanthene, fluorene, 1, 2, 4, 5-tetramethylbenzene, 4- tert -butylbenzoic acid, benzoic acid, 4-chloro-3-nitrobenzoic acid, 4-methoxybenzoic acid, 3, 4, 5-trimethoxybenzoic acid, 3-methyl-4-nitrobenzoic acid, 4-aminobenzoic acid, diphenyl sulphone, 2-ethylanthraquinone, thioxanthen-9-one, thianthrene, o-acetoacetanisidide, sorbic acid, 1, 4-dichloro-2-nitrobenzene, 1, 4-dibromobenzene, salicylamide, benzoin and trans -stilbene. Results of experimental measurements were combined with published solubility data taken from the published literature to derive Abraham model correlations for transfer of solutes into 2-methyl-1-butanol. The reported Abraham model correlations describe the observed solute transfer coefficients to within an overall average standard deviation of approximately 0.08 log units.